Respiratory Health Education through Interactive and Engaging Approach Involving Elementary Schoolchildren in Penjaringan, North Jakarta - Maria Mardalena Martini Kaisar; Anastasia Hangestu; Felicia Anggraini; Muhammad Fadli Muhyidin; Kevin Budijono; Soegianto Ali (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2026)
Air pollution poses a considerable threat to lung health worldwide, particularly in Jakarta, Indonesia’s largest urban center. Factors such as the extensive use of fossil-fueled vehicles, industrialization, and smoking contribute to poor air quality and affect children’s respiratory development and health. Therefore, this community service program aimed to educate elementary schoolchildren in Pejagalan, North Jakarta, about preventing the harmful effects of air pollution through comprehensive yet engaging learning methods. Pretests and posttests were used to evaluate students’ understanding and improvement in knowledge of the topic after the activity. This program integrated lecture-based education, an audiovisual approach through a visit to the Anatomy Museum, and game-based learning to enhance awareness. A total of 81 sixth-grade students participated in this activity under the supervision of the principal and seven teachers. A modest improvement was observed in several aspects of respiratory health, with female students demonstrating a marginally greater increase in knowledge, whereas male students exhibited a slight decrease. However, no significant difference was observed between pretest and posttest scores, either collectively (p = 0.756) or by gender (p = 0.243 for males and p = 0.196 for females), and knowledge remained within the moderate category. The findings suggested that students already had sufficient understanding of the topic at pretest; therefore, the increase in knowledge at posttest was not significant. Nevertheless, knowledge acquisition may be enhanced by optimizing content delivery and integrating diverse educational strategies, such as group-based simulations demonstrating the effects of smoking on lung color. Recognizing that early learning is essential for acquiring knowledge and fostering positive behaviors, this study underscores the importance of direct respiratory health education at an early age. This need was supported by favorable feedback from both students and teachers, indicating the value of this enjoyable learning activity. Therefore, continuous and sustainable respiratory health education through interactive approaches is essential for enhancing students’ knowledge acquisition and retention.